Factors Affecting Transparency And Accountability Of Village Fund Allocation Management - Neni Nurhayati; Amir Hamzah; Oktaviani Rita Puspasari; Sri Wijayatri (Kajian Akuntansi, 2022)
This study aims at analzing the effect of presentation of accountability reports and accessibility toward transparency and accountability of village allocation management (ADD). The method used in this research is descriptive and verification method. The sampling technique used is purposive sampling obtaind 102 respondents. The data analysis technique used is Structure Equation Modeling (SEM). The results of the study are presentation of accountability reports and accessibility has positive effect on transparency of village allocation management (ADD), presentation of accountability reports and accessibility has positive effect on accountability of village allocation management (ADD).